Break barriers, increase impact: equitable generation and dissemination of natural resource information in the Brazilian Amazon - Shanley, P.; Rodríguez Gaia, G. (2000)
Expansive growth in the logging, ranching and mining industries is swiftly transforming forests and forest dependent communities worldwide. To either resist or adapt to the powerful forces changing rural landscapes, small holders must respond to a glut of new information in an exceedingly short span of time. Under such conditions, the learning process must be consciously constructed so as to catalyse new ways of thinking about forest management effectively and quickly. The paper describes a research project in eastern Amazonia designed to assist rural communities evaluate the local costs and benefits associated with timber extraction and non-timber forest product use.